Advances and Challenges in Organic Electronics - Dumur, Frédéric; Goubard, Fabrice (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Organic Electronics is a rapidly evolving multidisciplinary research field at the interface between Organic Chemistry and Physics. Organic Electronics is based on the use of the unique optical and electrical properties of π-conjugated materials that range from small molecules to polymers. The wide activity of researchers in Organic Electronics is testament to the fact that its potential is huge and its list of potential applications almost endless. Application of these electronic and optoelectronic devices range from Organic Field Effect Transistors (OFETs) to Organic Light Emitting Diodes (OLEDs) and Organic Solar Cells (OSCs), sensors, etc. We invited a series of colleagues to contribute to this Special Issue with respect to the aforementioned concepts and keywords. The goal for this Special Issue was to describe the recent developments of this rapidly advancing interdisciplinary research field. We thank all authors for their contributions.